Prevalence and factors associated with the development of cardiorespiratory arrest in pregnant women (Research, Society and Development, 2021)
Introduction: Cardiopulmonary arrest (CPA) is a worldwide public health problem by which many lives are lost to annually in Brazil as a result of such problem. It is estimated that approximately 200,000 CPAs occur in Brazil per year, half of which are in healthcare facilities. In pregnant women it is estimated that this number is much lower, but its severity gets higher. The general objective of this research was to measure the prevalence of cardiopulmonary arrest in pregnant women. Methodology: The present study is a bibliographic research of the integrative literature review kind, using the PICo strategy to search for databases only BIREME and PUBMED being used. Results: Twenty-seven (27) studies were found, after applying the filters, thirteen (13) articles remained, out of which seven (07) were selected and included, six (06) in English and one (01) in Spanish. Conclusion: It is concluded that the occurrence of Cardiopulmonary Arrest in pregnant women, despite the anatomical and physiological changes that occur in the woman's body that predispose them to CPA or adverse cardiovascular events, the prevalence of such event in this population is rare. However, when it is occurs it can be catastrophic, thus characterizing an important public health issue and its closure depends on assistance executed with specific care.